CERITA RAKYAT “ASAL-USUL PULAU HALANG”: ANALISIS FUNGSI VLADIMIR PROPP - Yeni Maulina (Madah: Jurnal Bahasa dan Sastra, 2014)
Classical Malay literature in prose is classified in the form of folklore. The plot of folklore describes phenomena and object that exist, by explaining aspects of composition and structure, or aspects of the processes and changes. In other words, in order to determine the origin of an object or objects in folklore,  the phenomenon of the object or objects must be recognized first.  It is known as  original motifs of folklore. Folklore based on structuralism approach sought to facilitate understanding in terms of language or text used. In a fairy tale actors and its properties can be changed, but actions and their role remains the same. Vladimir Propp divided 31 functions of folklore by linking the events and actions of different that have the same meaning, or imply the same conduct. Folklore of the Asal Usul Pulau Halang has sixteen Vladimir Propp's functions. The function in this folklore  was developed starting from the first function, the function of IX, the function of X, the function of XII, the function of XIV, the function of the XV, the function of XVI, the function of the XIX, the  function of XX, the function of XXI, the function XXIII, the function of XXIV, the function of XXV, the function of the XXIX, the functions of XXX, and the functions of XXXI.   Karya sastra Melayu klasik yang berbentuk prosa tergolong  pada bentuk cerita rakyat. Alur cerita rakyat menggambarkan fenomena dan objek-objek yang ada, dengan menjelaskan aspek komposisi dan struktur, atau aspek proses dan perubahannya. Dengan kata lain, untuk mengetahui asal-usul suatu benda atau objek dalam cerita rakyat, terlebih dahulu mengenal fenomena benda atau objek tersebut. Berkaitan dengan hal tersebut, maka dikenal cerita rakyat bermotif asal-usul. Cerita rakyat berdasarkan pendekatan strukturalisme diusahakan untuk mempermudah pemahaman dari segi kebahasaan atau teks yang digunakan. Dalam sebuah cerita dongeng para pelaku dan sifat-sifatnya dapat berubah, tetapi perbuatan dan peran mereka tetap sama. Vladimir Propp membagi 31 fungsi dengan mengaitkan berbagai peristiwa dan perbuatan berbeda-beda tetapi mempunyai arti yang sama, atau mengisyaratkan perbuatan yang sama. Cerita rakyat ―Asal-usul Pulau Halang‖ memiliki enam belas fungsi Vladimir Propp. Fungsi dalam cerita rakyat ―Asal-usul Pulau Halang‖ dibangun mulai dari fungsi I, fungsi IX, fungsi X, fungsi XII, fungsi XIV, fungsi XV, fungsi XVI, fungsi XIX, fungsi XX, fungsi XXI, fungsi XXIII, fungsi XXIV, fungsi XXV, fungsi XXIX, fungsi XXX, dan fungsi XXXI.